1989
DOI: 10.1007/bf00922738
|View full text |Cite
|
Sign up to set email alerts
|

A Worksite smoking cessation intervention involving the media and incentives

Abstract: This study evaluated an attempt at 38 workplaces to help employees stop or reduce their levels of smoking. In past research, worksite support groups, in combination with a media smoking cessation program and self-help manuals, were found to be effective in helping employees quit smoking. Unfortunately, recidivism was found at the follow-up evaluations. The present study replicated the results of the previous worksite smoking cessation program with support groups, a television intervention, and self-help manual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Progression through stages of change was evaluated in one study, which found a progressive tendency towards higher stages of the quitting process (27). A reduction in the number of cigarettes smoked per day (2.5 and 3.6 cigarettes/day) was found in two (11,31) out of four studies evaluating this outcome (10,14). Another trial reported a 20% reduction in heavy smokers (more than 30 cigarettes/day) (34).…”
Section: Smoking Cessation Programsmentioning
confidence: 94%
See 4 more Smart Citations
“…Progression through stages of change was evaluated in one study, which found a progressive tendency towards higher stages of the quitting process (27). A reduction in the number of cigarettes smoked per day (2.5 and 3.6 cigarettes/day) was found in two (11,31) out of four studies evaluating this outcome (10,14). Another trial reported a 20% reduction in heavy smokers (more than 30 cigarettes/day) (34).…”
Section: Smoking Cessation Programsmentioning
confidence: 94%
“…Most (N=27) of them focused on tobacco control either exclusively (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21) or as part of a wider health promotion program (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). Sixteen health promotion programs focused exclusively (35)(36)(37)(38)(39)(40)(41)(42)(43) or in part (23-27, 31, 34, 43) on diet.…”
Section: Characteristics Of the Trialsmentioning
confidence: 99%
See 3 more Smart Citations